Challenges faced by the municipal water works management in improving water supply adequacy and distribution in Bontoc, Philippines - Magwilang, Epiphania B.; Paredes, Annie Lourie Yawan; Armas, Francisco C.; Bugnay, Helen Grace P.; Dagupen, Rose D. (Frontiers in Water, 2023)
Domestic water is indispensable for daily use, yet its effective management encounters numerous challenges that impact household consumers. This study aims to identify the challenges leading to supply inadequacy and uneven distribution, while proposing interventions to enhance water supply for households. The study employed surveys, interviews, and focus group discussions to gather comprehensive data on domestic water supply issues in rural communities in Bontoc, Philippines. The findings reveal two primary issues in these rural communities: supply inadequacy and unequal distribution. Supply inadequacy is attributed to factors such as wasteful water use, water scarcity during prolonged dry seasons, limited water sources, and population growth. Uneven distribution results from factors like landslides, illegal tapping, irregular water quality, insufficient monitoring of quantity and pressure, and inadequacies in the water distribution network layout. The study suggests several crucial actions for the local government unit (LGU) of Bontoc. These include augmenting water sources, implementing regular water supply monitoring, ensuring timely repairs, replacing old pipes, optimizing distribution pipeline layouts, enhancing water pressure, and rigorously enforcing municipal water ordinances. Furthermore, the study emphasizes the importance of household water management practices, such as responsible consumption, supply conservation, and recycling. The effective implementation of these interventions, through collaboration between the LGU and households, has the potential to ameliorate the constraints in domestic water supply and distribution. This collaborative approach is essential for improving supply management and addressing the current challenges faced by domestic water consumers.